Analisis Pengaruh Pendidikan, Upah Minimum Kabupaten Atau Kota (Umk), Dan Pdrb Terhadap Jumlah Penduduk Miskin Se-Karesidenan Madiun Tahun 2004-2014 - Widyawati, Wari Nila, Siti Fatimah N, SE, MSi (2017)
This study entitled "Analysis of Effect of Education, Minimum Wage District / City (MSEs), and the GDP against Poverty rates Se-residency of Madiun in 2004-2014". The objective is to analyze the influence of education, minimum wage districts / cities (MSEs), and the GDP of the number of poor people throughout the residency of Madiun in 2004-2014. The dependent variable in the form of the number of poor people (POV), while the independent variable in the form of education (EDUC), minimum wage districts / cities (MSEs), and the regional gross domestic product (GDP). This study uses secondary data with panel data regression analysis techniques. The results showed that the fixed effect model (FEM) is a panel data regression model is most appropriate. Based on test validity or the effect of the t test, education and regional gross domestic product significant negative effect on the number of poor people, while the minimum wage districts / cities did not significantly affect the number of poor people. Based on F test, education, minimum wage districts / cities, and regional gross domestic product simultaneously or jointly affect the number of poor people. The results of the regression output shows the adjusted R2 of 0.966542, or 96.65%, then the interpretation is 96.65% of the variation variable number of poor people (POV) can be explained by education (EDUC), regional gross domestic product (GDP) and wages minimum districts / cities (MSEs), and the rest of 3.35% variation of the variable number of poor people (POV) is explained by other variables that are not included in the model.